Generation of Janus kinase 1 (JAK1) conditional knockout mice. Issue 11 (19th October 2016) - Sakamoto, Kazuhito; Wehde, Barbara L.; Rädler, Patrick D.; Triplett, Aleata A.; Wagner, Kay‐Uwe
Abstract: The biological functions of the Janus kinase 1 (JAK1) are suggested to be pleiotropic since this signal transducer is ubiquitously expressed and coupled to a variety of cytokine receptors. Consequently, mice that are deficient in this tyrosine kinase were reported to die shortly after birth. To facilitate studies that address the biological and molecular functions of JAK1 during postnatal development, we performed gene targeting in embryonic stem cells and generated a Cre/lox‐based conditional knockout mouse model. Expression of Cre recombinase in the germline converted the Jak1 conditional knockout allele ( Jak1 fl ) into a null allele ( Jak1 ‐ ) that when subsequently crossed into homozygosity led to a complete absence of the JAK1 protein in developing embryos. JAK1 deficient embryos were visibly smaller starting at E15.5. Newborn pups exhibited signs of apnea and died within hours after birth. The examination of fibroblasts from conditional knockout embryos and their littermate wildtype controls expressing JAK1 showed that lack of this Janus kinase resulted in an impaired tyrosine phosphorylation and activation of the downstream Signal Transducers and Activators of Transcription (STATs) 1, 3, and 6. JAK1 conditional knockout mice will be an invaluable tool to study cytokine signaling during normal development and disease progression in adult animals.